Characteristic Features of the Agricultural Development During the Independence Years - Gafqaz, Agabalayev (Київський національний університет імені Тараса Шевченка, 2019)
The aim of the study is to analyze сcharacteristic features of the agricultural development during the independence years. Methods. The study used the method of comparative historical methods, statistics, analyze. Results. During the years of independence, the agricultural sector has undergone major changes, the role of those areas having strategic importance, export potential, and the creation of processing facilities has diminished. Distribution of soils to small populations does not allow the application of advanced methods, cultivation of agricultural products, use of productive seeds and animal breeds. Therefore, the share of this sector in GDP is low and does not meet the population’s demand for many products. Scientific novelty. Agrarian reforms during the years of independence have had a significant impact on the area and territorial structure of agriculture. Over the years, the areas of specialization formed in different regions have changed fundamentally, and there has been a decline in the production of strategic areas such as cotton, viticulture, tobacco production, tea-growing and cereal production. Instead, grain, potatoes, melon, fruit and vegetable crops cover a wide range of consumer needs. Currently, more than 60% of cultivated areas in the country are occupied by grain products. However, because of low productivity, the harvest does not meet domestic demand. The development of agriculture in the country requires the use of productive plants and animal species, the stocking up, storage, expansion of processing centres, and strengthening the logistics base. To ensure the food security of the population the uses of such opportunities also may create conditions. In the process of agricultural management, the demand for basic food products through domestic production is considered an important task. Grain, potatoes, fruit-growing and animal husbandry takes a huge place in the solution of this task. agricultural products are the foundation of the economic base in almost all cities and towns of the country regions.
Keywords: agriculture; agrarian reform; crop fields; food security; plant growing; livestock; specialization areas; regional development; domestic consumer goods